Self as coach : developing the best in you to develop the best in others - McLean, Pamela D
Become a more effective leader by discovering the resources you already have Pamela McLean, CEO and cofounder of the Hudson Institute for Coaching, has been at the forefront of the field for the past three decades, using clinical and organizational ps